Effects of a gel culture system made of polysaccharides (xanthan gum and locust bean gum) on in vitro bovine oocyte development and gene expression of the granulosa cells. Issue 7 (6th June 2021) - Sugimoto, Ayaka; Inoue, Yuki; Tanaka, Keisuke; Sinozawa, Akihisa; Shirasuna, Koumei; Iwata, Hisataka
Abstract: Xanthan gum (XG) and locust bean gum (LBG) are nontoxic polysaccharides that produce culture substrates. The present study examined the effect of XG‐LBG gel on in vitro bovine oocyte growth and gene expression in granulosa cells. Oocytes and granulosa cell complexes (OGCs) were cultured in vitro on plastic culture plate (Plate) or XG‐LBG gel for 16 days. OGCs formed a dome‐like cavity surrounding the oocytes on plate but formed a spherical follicle structure on XG‐LBG gel. The total granulosa cell numbers of the OGCs and their survival rate was greater for OGCs cultured on XG‐LBG gel than for those cultured on plate. Oocytes grown on XG‐LBG gels had higher lipid and mitochondrial content, as well as a larger diameter, than their plate counterparts. When oocytes grown in vitro were subjected to in vitro maturation and fertilization, the normal fertilization rate was significantly higher for oocytes developed on XG‐LBG gel than that of oocytes cultured on the plate counterpart. RNAseq of the granulosa cells revealed that genes associated with focal adhesion, phosphatidylinositol 3'‐kinase‐Akt and Hippo signaling, and regulation of actin cytoskeleton were upregulated in granulosa cells of OGCs cultured on XG‐LBG gel compared with those cultured on plate.